Gasochromic WO3/MoO3 sensors prepared by co-sputtering for hydrogen leak detection with long-lasting visible signal - Park, Chiwan; Han, Seung Ik; Duy, Le Thai; Yeasmin, Rubaya; Jung, Gwanggyo; Jeon, Dong Won; Kim, Woongchan; Cho, Sung Beom; Seo, Hyungtak (Sensors and Actuators B: Chemical, 2025)
Hydrogen is a renewable energy resource used as a fuel carrier with many advantages for future hydrogen economy systems. However, the safety of handling hydrogen fuel is of great concern due to explosion risks. Thus, in this study, a cost-effective WO3/MoO3-based gasochromic hydrogen sensor having a long-lasting signal (i.e., irreversible color change) is developed for detecting hydrogen leaks. Particularly, the active WO3/MoO3 compound film is deposited on a glass substrate by co-sputtering, and an ultrathin Pd catalyst layer for hydrogen gas decomposition is deposited on it using e-beam evaporation. Various characterizations are conducted to understand the structural, chemical, and optical properties of the WO3/MoO3-Pd films. In general, our WO3/MoO3-Pd sensor has excellent gas discoloration starting from 0.1 % of hydrogen concentration (in dry air) with fast response speed at room temperature. Besides, a DFT study further explains the sensing mechanism of our hybrid WO3/MoO3 structure. Those highlight the potential of our developed sensor for practical hydrogen sensing applications.
Keywords: Cosputtering; Fuel carriers; Gasochromic; Hydrogen leak detection; Hydrogen sensor; Irreversible; Long lasting; MoO 3; Renewable energies; Tungsten oxide; Gasochromic; Hydrogen sensors; Irreversible; Molybdenum oxide; Tungsten oxide